Діагностування розладів особистості у військовослужбовців в умовах війни - Євтушенко, Наталія Сергіївна; Твердохлєбова, Наталя Євгеніївна (ФОП "Жукова Ірина Віталіївна", 2024)
Війна – це збройна боротьба між державами (їх коаліціями) або соціальними, етнічними та іншими спільнотами; у переносному розумінні слова – крайня ступінь політичної боротьби, ворожих відносин між певними політичними силами. Не можливо оминути той факт, що війна гальмує наш звичайний життєвий ритм і підлаштовує нас під інші реалії існування. Події, що відбуваються, характеризуються високою інтенсивністю, напруженістю, швидкоплинністю. За цих умов психіка військовослужбовців функціонує на межі допустимих навантажень. Виснаження призводить до зниження ефективності їх діяльності в екстремальних умовах збройного протиборства, психологічних травм і психічних розладів короткочасного чи довготривалого характеру. Стрес, що виник у бойовій обстановці (первинний стрес) може посилюватися стресом пов'язаним із поверненням у звичайне середовище проживання (вторинний стрес). Сильні або тривалі впливи травматичного стресу в бойовій обстановці і стрес, зумовлений ситуацією повернення, можуть призвести до виникнення психічних розладів. Ризик розвитку посттравматичного синдрому після участі у воєнних діях є одним із найвищих. Успішність подолання негативних наслідків травматичного стресу у бойовій обстановці та соціально-психологічній адаптації у нових громадянських умовах залежить від багатьох факторів. Найбільшим чинником подолання негативного впливу травматичного події функціонування людини є його особистісні особливості. Однак ці особистісні особливості недостатньо вивчені і, крім того, незважаючи на те, що симптоматика посттравматичного синдрому може змінюватися або зберігатися протягом дуже тривалого часу.

War is an armed struggle between states (their coalitions) or social, ethnic and other communities; in a figurative sense of the word - an extreme degree of political struggle, hostile relations between certain political forces. It is impossible to get around the fact that war slows down our normal rhythm of life and adjusts us to other realities of existence. The ongoing events are characterized by high intensity, tension, transience. Under these conditions, the psyche of military personnel functions on the verge of permissible loads. Exhaustion leads to a decrease in the effectiveness of their activities in extreme conditions of armed confrontation, psychological trauma and mental disorders of a short-term or long-term nature.Combat stress (primary stress) may be exacerbated by stress associated with returning to normal environment (secondary stress). The strong or prolonged impact of traumatic stress in a combat environment and the stress caused by the return situation can lead to the onset of mental disorders. The risk of developing post traumatic syndrome after participating in hostilities is one of the highest. The success of overcoming the negative consequences of traumatic stress in a combat situation and social and psychological adaptation in new civilian conditions depends on many factors. The greatest factor in overcoming the negative impact of a traumatic event on a person's functioning is his personal characteristics. However, these personality traits are not well understood and, in addition, despite the fact that the symptoms of post-traumatic syndrome can change or persist for a very long time. For many years, personality disorders continue to be one of the most difficult sections of military psychiatry, both in clinical diagnostic and hospital expert moments, regardless of the conditions of service, that is, both in peacetime and during military operations. Predicting the likelihood of developing mental disorders in combatant accentuation should be based on a combination of such factors as the severity and duration of the traumatic impact, the severity of the combat transformation of the personality, and the length of time. A differentiated correction and medical and psychological rehabilitation of persons with combatant accentuation should be carried out, taking into account its type; it is especially needed upon the return of combatants to civilian life.
Diagnosis of personality disorders military servants in the conditions of war
Keywords: особистість; посттравматичний стресовий розлад; особовий склад; військовослужбовці; алгоритми; діагностика; specialty; post-traumatic stress disorder; personnel; military personnel; algorithm; diagnostics